Overexpression of Polysialylated Neural Cell Adhesion Molecule Improves the Migration Capacity of Induced Pluripotent Stem Cell‐Derived Oligodendrocyte Precursors. (28th July 2014) - Czepiel, Marcin; Leicher, Lasse; Becker, Katja; Boddeke, Erik; Copray, Sjef
Abstract : Overexpression of polysialylating enzyme sialyltransferase X (STX) was induced in iPSC‐derived oligodendrocyte precursors (OPCs) to stimulate production of polysialic acid‐neuronal cell adhesion molecules (PSA‐NCAMs), known to promote and facilitate OPC migration. STX‐overexpressing iPSC‐derived OPCs showed normal differentiation and maturation and were able to downregulate PSA‐NCAMs after becoming myelin‐forming oligodendrocytes. These findings suggest that the reach and efficacy of iPSC‐derived OPC transplantation will improve with stimulation of the OPC migration potential by specific gene modulation. Abstract : Cell replacement therapy aiming at the compensation of lost oligodendrocytes and restoration of myelination in acquired or congenital demyelination disorders has gained considerable interest since the discovery of induced pluripotent stem cells (iPSCs). Patient‐derived iPSCs provide an inexhaustible source for transplantable autologous oligodendrocyte precursors (OPCs). The first transplantation studies in animal models for demyelination with iPSC‐derived OPCs demonstrated their survival and remyelinating capacity, but also revealed their limited migration capacity. In the present study, we induced overexpression of the polysialylating enzyme sialyltransferase X (STX) in iPSC‐derived OPCs to stimulate the production of polysialic acid‐neuronal cell adhesion molecules (PSA‐NCAMs), known to promote and facilitate the migration of OPCs. The STX‐overexpressing iPSC‐derived OPCs showed a normal differentiation and maturation pattern and were able to downregulate PSA‐NCAMs when they became myelin‐forming oligodendrocytes. After implantation in the demyelinated corpus callosum of cuprizone‐fed mice, STX‐expressing iPSC‐derived OPCs demonstrated a significant increase in migration along the axons. Our findings suggest that the reach and efficacy of iPSC‐derived OPC transplantation can be improved by stimulating the OPC migration potential via specific gene modulation.